Gas diffusion electrodes improve hydrogen gas mass transfer for a hydrogen oxidizing bioanode. Issue 12 (3rd October 2017) - Rodenas, Pau; Zhu, Fangqi; ter Heijne, Annemiek; Sleutels, Tom; Saakes, Michel; Buisman, Cees
Abstract: Background: Bioelectrochemical systems (BESs) are capable of recovery of metals at a cathode through oxidation of organic substrate at an anode. Recently, also hydrogen gas was used as an electron donor for recovery of copper in BESs. Oxidation of hydrogen gas produced a current density of 0.8 A m ‐2 and combined with Cu 2+ reduction at the cathode, produced 0.25 W m ‐2 . The main factor limiting current production was the mass transfer of hydrogen to the biofilm due to the low solubility of hydrogen in the anolyte. Here, the mass transfer of hydrogen gas to the bioanode was improved by use of a gas diffusion electrode (GDE). Results: With the GDE, hydrogen was oxidized to produce a current density of 2.9 A m ‐2 at an anode potential of –0.2 V. Addition of bicarbonate to the influent led to production of acetate, in addition to current. At a bicarbonate concentration of 50 mmol L ‐1, current density increased to 10.7 A m ‐2 at an anode potential of –0.2 V. This increase in current density could be due to oxidation of formed acetate in addition to oxidation of hydrogen, or enhanced growth of hydrogen oxidizing bacteria due to the availability of acetate as carbon source. The effect of mass transfer was further assessed through enhanced mixing and in combination with the addition of bicarbonate (50 mmol L ‐1 ) current density increased further to 17.1 A m ‐2 . Conclusion: Hydrogen gas may offer opportunities as electron donor for bioanodes, with acetate as potential intermediate, at locations where excess hydrogen and no organics are available. © 2017 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.